MAPPING INDUSTRI KREATIF KECAMATAN KEDUNGKANDANG KOTA MALANG - Baroroh Lestari (Universitas Sebelas Maret, 2020)
The creative industry is one sector that is currently being intensified by the government. It is hoped that each region in Indonesia has a creative industry that can be developed. This study aims to map the creative industry in Kedungkandang District, Malang City which refers to the 2015 version of the Indonesian Business Sector Standard (KBLI). This research was conducted in Kedungkandang District, Malang City with a research focus on 32 creative industries. Then to find out the description of the creative industry in Malang, the social mapping method is used. The results showed that Kedungkandang District is a sub-district with the lowest creative industry players in Malang City. In Kedungkandang District, only a few sub-sectors of the creative industry have developed well, namely crafts, fashion and culinary. The knitting craft industry is an alternative for developing the creative industry in Kedungkandang District. With a focus on the creative industry, Kedungkandang District will have a unique characteristic of Kedungkandang District.Key words: Creative, Industries, Kedungkandang sub-district